1993
DOI: 10.1038/clpt.1993.85
|View full text |Cite
|
Sign up to set email alerts
|

Single-dose disulfiram inhibition of chlorzoxazone metabolism: A clinical probe for P450 2E1

Abstract: Disulfiram and its reduced metabolite diethyldithiocarbamate have been identified previously as selective mechanism-based inhibitors of human liver microsomal cytochrome P450 2E1 in vitro. In animals, a single oral dose of disulfiram has been shown to produce a rapid and selective inactivation of hepatic P450 2E1 content and catalytic activity in vivo. This investigation explored the efficacy of single dose disulfiram as an inhibitor of human P450 2E1 activity in vivo. Clinical P450 2E1 activity was assessed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
50
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(58 citation statements)
references
References 0 publications
8
50
0
Order By: Relevance
“…CYP2E1 activity was determined by measuring the hydroxylation of CZX to 6-OH-CZX, as described previously by Kharasch et al (37). All samples were tested in triplicate.…”
Section: Screening For Cyp2e1 Inhibitorsmentioning
confidence: 99%
“…CYP2E1 activity was determined by measuring the hydroxylation of CZX to 6-OH-CZX, as described previously by Kharasch et al (37). All samples were tested in triplicate.…”
Section: Screening For Cyp2e1 Inhibitorsmentioning
confidence: 99%
“…Activity of CYP2E1 is also modulated by various physiological determinants, such as obesity [7] , fasting [7] and liver dysfunction [8] and can be induced by ethanol [9] . In contrast, dietary isothiocyanates [10] and garlic [11,12] , as well as some drugs, such as disulfiram [13] and chlormethiazole [14] , inhibit its activity. A number of environmental factors may thus modify the cancer risk through altered CYP2E1 enzyme activity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a previous study has shown that the activity of CYP2E1 is modulated by various physiological determinants, such as obesity (O'Shea et al, 1994), fasting (O'Shea et al, 1994), and liver dysfunction (Dilger et al, 1997), and can be induced by ethanol (Girre et al, 1994). In contrast, dietary isothiocyanates (Leclercq et al, 1998), and garlic (Reicks and Crankshaw, 1996;Yang et al, 1994), as well as some drugs, such as disulfiram (Kharasch et al, 1993), and chlormethiazole (Gebhardt et al, 1997), inhibit CYP2E1 activity.…”
Section: Discussionmentioning
confidence: 99%